Strategies for Bridging Cross-Cultural Barriers for International Students' success in American Asynchronous on-line Degree Programs - Chukhlomin, Valeri; Deshpande, Anant; Chandra, Bidhan (South African Journal of Higher Education, 2016)
The increasing popularity and acceptance of asynchronous on-line programs has led to an increase in cross-border international collaboration and partnerships between American and international institutions of higher learning to offer on-line dual degree programs for international students. However, the success of these partnerships depends on the ability of the international students to understand and navigate the many cultural differences between the two systems, and for American institutions to provide assistance. As an institution initiating and participating in such international programs, the Center for Distance Learning(CDL) at SUNY Empire State College in New York,USA, has sought to accommodate and assist international students studying at remote U.S.universities from their home countries. To this end, CDL formed an international distance learning group charged with fostering inter-institutional collaboration. One effort of this group was the development of “3B” (Bridging Bilingual/Bicultural) courses that use Web 2.0 tools, such as wikis, blogs, videoconferencing, lecture capture, asynchronous discussions, and virtual worlds. The paper presents three retrospective case studies and discusses how the “3B” model has been used with success to assist international students acculturate to distance learning.